OPTIMASI PENJADWALAN PROYEK DENGAN PENYEIMBANGAN BIAYA MENGGUNAKAN KOMBINASI CPM DAN ALGORITMA GENETIKA - Riza Arifudin (Department of Informatics, Universitas Diponegoro, 2011)
The project scheduling must be prepared systematically by using resources effectively and efficiently so that project objectives can be achieved optimally. This research aimed to examine the application of combinaton CPM and genetic algorithms to solved optimization problems in a project scheduling with the leveling of costs and designing a software. CPM is one of method to schedule the project that produce the shortest time. In this study of CPM combined with genetic algorithm to perform scheduling. Genetic algorithms are search methods that mimic the process of solution of natural selection and genetics. The allocation of activities is determined based on the earliest start time and latest start time by taking into account the cost of resources in each period of the project. Project scheduling and optimal criterion used is minimizing the cost of deviations from the average total project cost. Results obtained in this research is that the cost of scheduling with deviations smaller than the scheduling with CPM alone thus generated a shorter project schedules and project cost per day is also more equitable. This Scheduling method can be alternative decisions for the contractor in project implementation.